2009
DOI: 10.5511/plantbiotechnology.26.197
|View full text |Cite
|
Sign up to set email alerts
|

Two-component high-affinity nitrate transport system in barley: Membrane localization, protein expression in roots and a direct protein-protein interaction

Abstract: Nitrate is one of the major sources of nitrogen for higher plants and is taken up from the soil by active transporters coupled with H ϩ across the plasma membrane (PM) of root cells. Nitrate uptake systems have been classified into two groups: low-affinity transport systems (LATS) and high-affinity transport systems (HATS). The LATS contribute to nitrate uptake at high nitrate concentrations above 1 mM whereas the HATS operate at micromolar concentrations of external nitrate and display MichaelisMenten kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 32 publications
5
37
0
Order By: Relevance
“…gene expression and HATS activity, on the other hand Ishikawa et al, 2009). These data support the previous proposal that posttranscriptional regulatory mechanisms participate in the control of the HATS, because expression of a 35S::NpNRT2.1 or RolD:: NpNRT2.1 transgene in N. plumbaginifolia did not prevent down-regulation of the HATS activity by high NH 4 NO 3 supply (Fraisier et al, 2000).…”
Section: Nrt21 Posttranscriptional Regulation In Arabidopsissupporting
confidence: 80%
See 1 more Smart Citation
“…gene expression and HATS activity, on the other hand Ishikawa et al, 2009). These data support the previous proposal that posttranscriptional regulatory mechanisms participate in the control of the HATS, because expression of a 35S::NpNRT2.1 or RolD:: NpNRT2.1 transgene in N. plumbaginifolia did not prevent down-regulation of the HATS activity by high NH 4 NO 3 supply (Fraisier et al, 2000).…”
Section: Nrt21 Posttranscriptional Regulation In Arabidopsissupporting
confidence: 80%
“…More recently, the abundance of the Arabidopsis NRT2.1 protein in the root plasma membrane was reported to be little affected by treatments that strongly regulate both NRT2.1 transcript accumulation and NO 3 2 HATS activity . In barley too, changes in HvNRT2.1 protein were not correlated with those of HvNRT2.1 transcript accumulation during induction by NO 3 2 (Ishikawa et al, 2009). Finally, studies on NRT2 homologs in lower eukaryotes, e.g.…”
mentioning
confidence: 99%
“…Nevertheless, the importance of such a regulation has been supported by data obtained in tobacco (Fraisier et al 2000), barley (Ishikawa et al 2009) and A. thaliana Laugier et al 2012). In the later species, ectopic expression of NRT2.1 actually resulted in a high and almost constant mRNA level in the roots, which did not prevent downregulation of NO 3 − HATS activity by high N supply.…”
Section: Post-transcriptional Regulation Of Root N Transportersmentioning
confidence: 94%
“…8 The NAR2 protein plays a role in establishing HATS activity by targeting NRT2 to the plasma membrane. 12,13 In the rnc1 mutant of Arabidopsis, it was suggested that an aspartate residue in the central loop of NAR2 was important for HATS activity. 14 Immunological results demonstrated an oligomer, proposed to contain a tetramer consisting of two subunits each of AtNRT2.1 and AtNAR2.1, was active in HATS.…”
Section: Function Of Nar2 As a Nitrate Accessory Proteinmentioning
confidence: 99%
“…13 In barley, a direct protein-protein interaction was shown to occur between the HvNRT2.1 C-terminal, S463A, and the HvNAR2.3 central region. 12 However, it is difficult to determine if this serine is a key residue because it is not conserved in AtNRT2.1 and HvNRT2.1 C-terminal. 12 In rice roots we detected some differences in the tissue specific expression of OsNAR2.1 and its interacting NRT2 members.…”
Section: Function Of Nar2 As a Nitrate Accessory Proteinmentioning
confidence: 99%